POTENTIALS OF SAWDUST AND DISPOSED WATER SACHET WASTES FOR WOOD PLASTIC COMPOSITE PRODUCTION - Saka, Moruff Gbolagade; Dongs, Y. D.; Aujara, Y. I. (FUDMA Journal of Sciences, 2022)
The study investigated the potential of sawdust and disposed water plastics for the production of wood plastic composite. The sawdust was obtained from the plank market in Yola, while, the water sachets were hand-picked within the Modibbo Adama University premises. The gathered sawdust were sieved into 1.0 and 2.0 mm particle sizes, thoroughly mixed with already melted water sachet plastics at a ratio of 1:25 (100: 2500 ml) and 1:30 (100:3000 ml) respectively,. The mixtures were heated at (105.20 C,) and then filled into  an already constructed oiled Aluminum mold of size 1.5 x 6 x 15 cm. Pressure was applied for two hours to compress the composite before removal from the mold. The samples were then trimmed according to sample size requirement, for mechanical and physical property properties tests. The results revealed that, the plastic composite produced from 2mm sawdust particles and mixed at ratio of 1:25 has the highest mean hardness (14.99 ± 3.54 MPa), The mean highest impact strength (1.24 ± 0.12 J) was obtained in the sample with particle size 1 mm and plastic ratio of 1:30, while, the highest mean water absorption percentage (2.27 ± 0.132 ) was obtained in particle size 2  mm and plastic ratio of 1:25.The Analysis of variance conducted shows that, sawdust particle size and mixing ratio had significant effect on both physical and mechanical properties of the produced plastic composite (p < 0.05). The study had demonstrated that the use of disposed sachet water plastics and sawdust waste
Keywords: Wood plastic composite, Impact strength, Absorption, Particle size